2012
DOI: 10.1002/polb.23046
|View full text |Cite
|
Sign up to set email alerts
|

The friction coefficient on polycarbonate as a function of the contact pressure and nanoscale roughness

Abstract: During dry friction the rheological behavior at the interface between a polymer surface and a rigid indenter is linked to the local pressure and the roughness of the surface of the indenter. This study on polycarbonate reports experimental results obtained at ambient temperature using rigid, spherical glass indenters of various radii. In a first step, a plot of the experimental friction coefficient l versus the mean contact pressure p mean showed that below the yield stress (p mean < 100 MPa) the intrinsic fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…6b plots the experimental mean contact pressure p mean against the ratio a/R or tan(b) for several indenters. Previous work showed that these data follow the classical laws of contact mechanics [19]. It was concluded that the PC surface is in its elastic regime for p mean o30 MPa, in its elasto-plastic regime for 30 MPao p mean o150 MPa and in its fully plastic regime for p mean 4150 MPa.…”
Section: Modeling Approachsupporting
confidence: 52%
See 4 more Smart Citations
“…6b plots the experimental mean contact pressure p mean against the ratio a/R or tan(b) for several indenters. Previous work showed that these data follow the classical laws of contact mechanics [19]. It was concluded that the PC surface is in its elastic regime for p mean o30 MPa, in its elasto-plastic regime for 30 MPao p mean o150 MPa and in its fully plastic regime for p mean 4150 MPa.…”
Section: Modeling Approachsupporting
confidence: 52%
“…Sliding friction experiments are performed in our experimental set-up using an original in situ display fully described elsewhere [19]. The motion of the tip and normal load F n are monitored, while the tangential force F t is recorded and the normal contact area S of a transparent material is visualized and analyzed with a built-in imaging system (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations